Spatial patterns of agricultural productivity - Wood, Stanley; Guo, Zhe; Wood-Sichra, Ulrike (International Food Policy Research Institute, 2016)
The previous chapter examined several measures of productivity, primarily in terms of their evolution over time, and reported those changes by countries and subregions. However, the conditions under which agriculture is practiced and specific production systems predominate are highly diverse spatially, even within a single country. This chapter, therefore, examines patterns of agricultural productivity not only at a greater spatial resolution but also in terms of the spatial distribution of specific production systems. We first summarize some of the reasons for growing interest in the spatial dimensions of agriculture, briefly review the general characteristics of the spatial datasets used, and then describe the specific production system schema underpinning the analyses presented in this and subsequent chapters. In the following sections we describe the spatial variability of key factors shaping the productivity of production systems, examine the overall value of (crop) production and associated spatial patterns of land and labor productivity, and briefly discuss the projected effects of climate change spatially. In the final section, we summarize our findings and their implications for prioritizing and targeting interventions, especially in the context of planning for knowledge and technology spillover across domains, countries, and subregions.